Service quality enhancement of Bangladesh Islamic Banks: an application of Quality Function Deployment (QFD) - Islam, Muhummad Khairul; Islam, Rafikul; Mohd. Israil, Khaliq Ahmad (2019)
The main purpose of this study is to identify the customers’ requirements, the corresponding technical requirements and aligning both of these requirements by using a well-known service quality improvement tool, namely, Quality Function Deployment (QFD). In this study, a mixed method approach were used where, questionnaires survey and interviews were conducted for data collection. Data were collected from customers, employees and executive officers (altogether 347 in number of respondents) from seven Islamic banks on personal contact basis. From the data analysis in the first stage, this research revealed that customers’ perceived expectations are higher than the services delivered. Later on, the researcher compiled altogether 45 customers’ requirements (‘what’) and 47 technical requirements (‘how’) for further enhancement of service quality of Islamic banks in Bangladesh. Finally, the QFD exercise was carried out to prioritize the technical requirements (‘hows’), which will eventually guide implementation of the necessary measures to improve the overall quality of the Islamic banks in Bangladesh. This research contributes to the existing body of knowledge in field of academics and findings are expected to provide guidelines for enhancing satisfaction level of customers of the Islamic banks in Bangladesh.